أثر الأنشطة البشرية على البيئة الجافة في شمال شرق بغداد - معروف، فلاح جمال; علي، سلام فاضل (جامعة البصرة - كلية الآداب, 2013)
أن للأنشطة البشرية أثارا واضحة في البيئة الطبيعية لمنطقة الدراسة وهي منطقة هامشية (Margin) للسلطات البلدية واقل خضوعا لنشاطها وتطبيقا لقوانينها وإدارتها، اذ أن لتلك الأنشطة دورا بارزا وأثرا واضحا في تدهور البيئة الطبيعية من خلال ما تسببه من تلوث وتدهور بيئي فالأنشطة التي تقوم في بيئة المنطقة الجافة تؤثر سلبا فيها حسب طبيعة كل نشاط، وتبدأ مؤثرات هذه الأنشطة بتدهور البيئة الطبيعية من خلال تلويثها لهوائها ومائها وتربتها وهذه المؤثرات تؤثر في الإنسان بشكل أو باخر فتسبب له المرض وأحيانا الوفاة لما تعانيه من نقص كبير في معظم الخدمات الضرورية وتتراكم فيها النفايات والازبال بل هي في كثير من الأحيان مصدر لأرزاقهم ومحاور لصراعاتهم، فضلا عن عدم توافر تصريف صحي للمياه القذرة، والاكثر من ذلك افتقارها الى شبكة الماء الصافي أصلا مما يجعلها عبارة عن أكوام من القاذورات والركامات تتخللها كتلة من المساكن العشوائية غير الصحية. تضم أعدادا ضخمة من العاطلين وشبه العاطلين عن العمل. ومن هنا ومع تعدد الدراسات الحضرية بل تضخمها فان منطقة الحافات ذات البية الجافة ظلت تعاني وتعتصر آلامها في ظل. قله هم الذين أشاروا أو ذكروا منطقة الحافات بالدراسة. \ ونظرا لصعوبة وعمق مشكلة التدهور البيئي الناجم عن النشاط البشري الذي شكل خللا بيئيا واجتماعيا في النسيج الحضري في منطقة الدراسة من هنا ظهرت الحاجة إلى دراسة لتقييم نوعية الأنشطة البشرية القائمة لذلك سوف يتناول هذا البحث التأثيرات الناجمة عن تلك الأنشطة على البيئة الطبيعية. The human activities have got distinct effects on the natural environment of - the circle in question. The municipality authority considers it as a marginal circle and it controls it partially regarding activity, laws and management. Therefore, those human activities play a major role in clearly causing environmental pollution affecting the deterioration of the natural environment. The activities practiced in the arid circle environment have got a negative effect according to the nature of each activity. They begin by polluting the air, the water, and the soil of that circle, and consequently affecting man passively causing him diseases and probably death. It is clear that this natural environmental circle lacks the necessary services and therefore garbage, waste and scrap are accumulated. However, such accumulated harm materials become mostly a source for their living and debates that may cause struggles among them. In addition, the unavailability of drainage, sanitation, and lack of hygienic drinking water pipes that have been changed into piles of dirt in the middle of which are unhygienic houses built randomly. These houses are resided by a huge number of unemployed or semi-unemployed people. Few studies have given much care for dealing with such marginal environmental arid circles. \ Since the human activity has caused difficulty and depth to the environmental deterioration which leads to an environmental and social problem in the urban structure of the circle of this study, an urgent need come out to study and evaluate the kinds of the human activities existing. Therefore, this paper is to investigate the effects resulted from these activities on the natural environment.
Keywords: النشاط البشري -- صحة البيئة -- العراق